Neurosteroids in Schizophrenia: Pathogenic and Therapeutic Implications - Cai, HuaLin; Cao, Ting; Zhou, Xiang; Yao, Jeffrey K. (Frontiers in Psychiatry, 2018)
Neurosteroids are a group of important endogenous molecules affecting many neural functions in the brain. Increasing evidence suggests a possible role of these neurosteroids in the pathology and symptomatology of schizophrenia and other mental disorders. The aim of this review is to summarize the current knowledge about the neural functions of neurosteroids in the brain, and to evaluate the role of the key neurosteroids as candidate modulators in the etiology and therapeutics of schizophrenia. The present paper provides a brief introduction of neurosteroid metabolism and distribution, followed by a discussion of the mechanisms underlying neurosteroid actions in the brain. The content regarding the modulation of the GABAA receptor is elaborated, given the considerable knowledge of its interactions with other neurotransmitter and neuroprotective systems, as well as its ameliorating effects on stress that may play a role in the schizophrenia pathophysiology. In addition, several preclinical and clinical studies suggested a therapeutic benefit of neurosteroids in schizophrenia patients, even though the presence of altered neurosteroid pathways in the circulating blood and/or brain remains debatable. Following treatment of antipsychotic drugs in schizophrenia, therapeutic benefits have also been linked to the regulation of neurosteroid signaling. Specifically, the neurosteroids such as pregnenolone and dehydroepiandrosterone affect a broad spectrum of behavioral functions through their unique molecular characteristics and may represent innovative therapeutic targets for schizophrenia. Future investigations in larger cohorts with long-term follow-ups will be required to ascertain the neuropsychopharmacological role of this yet unexploited class of neurosteroid agents.